Exhaled breath acetone for predicting cardiac and overall mortality in chronic heart failure patients. (7th May 2020) - Marcondes‐Braga, Fabiana G.; Gioli‐Pereira, Luciana; Bernardez‐Pereira, Sabrina; Batista, Guilherme L.; Mangini, Sandrigo; Issa, Victor S.; Fernandes, Fabio; Bocchi, Edimar A.; Ayub‐Ferreira, Silvia M.; Mansur, Alfredo J.; Gutz, Ivano G.R.; Krieger, Jose E.; et al.
Abstract: Aims: Exhaled breath acetone (EBA) has been described as a new biomarker of heart failure (HF) diagnosis. EBA concentration increases according to severity of HF and is associated with poor prognosis, especially in acute decompensated HF. However, there are no data on chronic HF patients. The aim is to evaluate the role of EBA for predicting cardiac and overall mortality in chronic HF patients. Methods and results: In GENIUS‐HF cohort, chronic patients were enrolled between August 2012 and December 2014. All patients had left ventricular ejection fraction ≤ 50%, and the diagnosis was established according to Framingham criteria. After consent, patients were submitted to clinical evaluation and exhaled breath collection. EBA identification and quantitative determination were done by spectrophotometry. The clinical characteristics associated with acetone were identified. All participants were followed for 18 months to assess cardiac and overall mortality. Around 700 participants were enrolled in the current analysis. Patients were 55.4 ± 12.2 years old, 67.6% male patients, and 81% New York Heart Association I/II with left ventricular ejection fraction of 32 ± 8.6%. EBA median concentration was 0.6 (0.3–1.2) ug/L. Acetone levels increased with the number of symptoms of HF and were associated with right HF signs/symptoms and liver biochemical changes. EBA at highest quartile (EBA > 1.2ug/L) was associated with a significantly worse prognosis (log rank test, P  < 0.001). Cox proportional multivariable regression model revealed that EBA > 1.20ug/L was an independent predictor of cardiac ( P  = 0.011) and overall ( P  = 0.010) mortality in our population. Conclusions: This study shows that EBA levels reflect clinical HF features, especially right HF signs/symptoms. EBA is an independent predictor of cardiac and overall mortality in chronic HF patients.